Pelatihan Pembuatan PMT Berbasis Pangan Lokal Pada Ibu Balita di Wilayah Kerja Puskesmas Wanaraja - Siti Nurcahyani Ritonga; Nofita Setiorini Futri Purwanto; Ira Nufus Khaerani (Lembaga Pengembangan Kinerja Dosen, 2024)
One of the causes of stunting and wasting problems in toddlers is a lack of nutritional intake over a long period of time. Stunting is caused by malnutrition in the womb and usually begins to appear when the child is two years old. One effort that can be made is to increase knowledge about nutrition and good eating patterns. Adequate nutritional intake does not have to be expensive, and fulfilling adequate food intake is very important for women before marriage. This is because women will be mothers who educate and raise children. Mothers have an important role in choosing food for the family, so knowledge about nutrition is very important. The aim is for the community or target partners to know in advance about the problems that exist in the target location and to introduce solutions to the partner's problems. In this activity, there is education or counseling for mothers of toddlers and cadres about stunting and how to control it. The method used is a demonstration of making local food products as an alternative snack for toddlers. The activity was attended by 34 mothers of toddlers in the Wanaraja Community Health Center area. The stages carried out from start to finish are an assessment of the local food potential of the local area, a cooking demonstration for making PMT and an evaluation of implementation. The results of the activity showed that 34 mothers of toddlers who took part in the training implemented the creation of local food PMT menus in their respective places. Community health centers need to create a continuous training schedule so that cadre mothers are more motivated to make PMT menus from local food.